Zadoff-chu sequence based preamble design of fbmc/oqam for 5g - Krishna Namani, Vamshi; Arthi, R (International Journal of Engineering and Technology, 2018)
The Spectrum effectiveness for 5G networks can be accomplished by Filter Bank Multi Carrier / Orthogonal Quadrature Amplitude Modulation (FBMC / OQAM) that avoids the benefit of guard band. FBMC is very considerate to Carrier Frequency Offset (CFO) and Timing Offset (TO). This paper suggests Zadoff-chu (ZC) sequence based preamble or pilot is accustomed to design the FBMC frame for synchronize more with receiver to achieve sufficient channel inference and phase tracking which reduces the carrier frequency and timing synchronization. This method helps to influence the out of band emissions and conceive non-orthogonal waveforms to investigate the overall system performance such as Bit Error Rate (BER) over AWGN channels. The performance measuresbeing Complementary Cumulative Distribution Curve (CCDF) for FBMC signal with different multicarrier to evaluate the Peak to Average Power Ratio (PAPR) has been achieved by simulation. The simulation outcomeshows that FBMC outperforms well when analyzed with other multicarrier systems.Â Â